Mathematical models of wheel turning processes road construction vehicles - Sukharev R.Yu. (Научно-технический вестник Брянского государственного университета)
The construction of highways is a complex, multi-stage process. Most of the construction works are carried out according to the projects of structures and quite high requirements are imposed on the quality of execution. The fulfillment of these requirements is associated with great difficulties in view of the limited accuracy of the road construction machine itself, the lack of on-board control systems and the limited capabilities of the human operator, who is unable to determine the required exact parameters of the structure being built «by eye». To meet the requirements, three-dimensional control systems are used, which allow determining 3 coordinates of the working order of the machine – the vertical coordinate and the location of the machine on the construction site. At the same time, the digital project of the constructed structure should be the setter in such a system. The system determines the current position and compares it with the project. On the basis of this information, a control effect on the operating organ of the machine is formed. The course of movement and the speed of the machine when using such systems are determined by the machine operator. Further development of these systems should be four-dimensional systems – in which all control actions are assigned to the control system, starting from calculating the trajectory of the machine, choosing the speed, determining the required number of passes and ending with controlling the position of the working body of the machine at each moment of time. For the functioning of these systems, adequate mathematical models of the turning processes of road construction machines with different steering options are necessary.